2010
DOI: 10.1021/jp103288x
|View full text |Cite
|
Sign up to set email alerts
|

Two-Dimensional Heterospectral Correlation Analysis of X-ray Photoelectron Spectra and Infrared Spectra for Spin-Coated Films of Biodegradable Poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) Copolymers

Abstract: We investigated the thermal behavior of spin-coated films of biodegradable poly(3-hydroxybutyrate-co-3-hydroxyhexanoate) (P(HB-co-HHx)) copolymers at the molecular level. To better understand details of thermal behavior of spin-coated films of P(HB-co-HHx) copolymers, we applied two-dimensional (2D) correlation analysis to the spectra of P(HB-co-HHx) (HHx = 12.0, 10.0, and 3.8 mol %) copolymers during the heating process from 30 to 150 degrees C as obtained by temperature-dependent infrared-reflection absorpti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
18
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(18 citation statements)
references
References 24 publications
0
18
0
Order By: Relevance
“…SFG is therefore established as a sensitive probe of polymer surface structure. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, it is often challenging to separate the effects of orientation from changes in concentration in the SFG signal. In this study we will therefore combine IR absorption and SFG spectroscopy to study the drying process of butyl acrylate PSAs containing varying amounts of acrylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…SFG is therefore established as a sensitive probe of polymer surface structure. [11][12][13][14][15][16][17][18][19][20][21][22][23][24] However, it is often challenging to separate the effects of orientation from changes in concentration in the SFG signal. In this study we will therefore combine IR absorption and SFG spectroscopy to study the drying process of butyl acrylate PSAs containing varying amounts of acrylic acid.…”
Section: Introductionmentioning
confidence: 99%
“…Choi et al demonstrated the details of thermal behavior of spin-coated films of biodegradable poly(3-hydroxybutyrate- co -3-hydroxyhexanoate) or P(HB- co -HHx) (HHx = 12.0, 10.0, 3.8 mol%) copolymers by using 2DCOS (Choi et al, 2010). The temperature-dependent infrared-reflection absorption (IRRAS) spectra of a spin-coated film of P(HB- co -HHx) (HHx = 12.0 mol%) copolymer, which were measured during the heating process, are shown in Figure 2.…”
Section: Application Of 2dcos In Polymer Studiesmentioning
confidence: 99%
“…Three possible possibilities in 2D hetero-correlation analysis are hetero-spectral correlation (Kim et al, 2006a; Choi et al, 2010; Katayama et al, 2010; Smirnova et al, 2011; Park et al, 2012; Ryu et al, 2012; Shinzawa et al, 2012), hetero-perturbation (or hybrid) correlation (Wu et al, 2002, 2006), and hetero-sample correlation (Czarnik-Matusewicz et al, 2009; Pi et al, 2010). Among them, 2D hetero-spectral correlation is the most active field in applications of 2D hetero-correlation analysis.…”
Section: Application Of 2dcos In Polymer Studiesmentioning
confidence: 99%
See 1 more Smart Citation
“…It is possible to apply 2D heterospectral analysis to the correlation not only between closely related spectroscopic measurement, such as IR and Raman spectra, but also between completely different types of spectroscopic or physical techniques. For example, 2D heterospectral between X-ray photoelectron spectroscopy (XPS) and IR spectroscopy (104) and between wide angle X-ray scattering (WAXS) and IR spectroscopy (109) were used to investigate semi-crystalline copolymers under increasing temperature and to characterize the specific chemical interactions existing in weakly interacting closed-loop block copolymer, respectively. Figure 11 shows heterospectral XPS/IR correlation spectra of spin-coated film of P(HB-co-HHx) copolymer with temperature increases.…”
Section: D Heterocorrelation Analysismentioning
confidence: 99%